Mahkota tiruan metal porselen anterior dengan modifikasi tepi porselen - Roeli Ardi Andries; Farisza Gita (DiscoverSys Inc., 2010)
Metal ceramic crown is a very popular restoration used in dentistry for itsadvantageous properties. However, when metal ceramic crown is used at anteriorregion, grey area usually occured around the margin area and cause poor esthetics.The esthetic of metal ceramic crown can be improved by modifying the porcelainmargin. Therefore providing better translucency of cervical area the gingival will notaffected by metal coping. Margin preparation for porcelain should be shoulder typewith internal round angle and is made about 90-100Â° to root surface with 1-1.5 mmthickness. This case report discussed about the management of metal ceramic dowelcrown on anterior teeth with modification of porcelain margin to achieve restorationwith excellent esthetics.